Comparing the therapeutic potentials of Lactobacillus johnsonii vs. Lactobacillus acidophilus against vulvovaginal candidiasis in female rats: an in vivo study - ElFeky, Dalia Saad; Awad, Alaa Reda; Shamseldeen, Asmaa Mohammed; Mowafy, Hagar Lotfy; Hosny, Sara Adel (Frontiers in Microbiology, 2023)
Background: Vulvovaginal candidiasis (VVC) is a highly prevalent illness affecting women globally. Lactobacilli, which make up the majority of healthy vaginal microbiota (VMB), serve as a powerful barrier against infections. Probiotic therapy has been recommended for the treatment or prevention of VVC. Aim of work: To compare the in vivo therapeutic eﬀects of Lactobacillus johnsonii (B-2178) versus Lactobacillus acidophilus (LA-5®) on VVC in a rat model, particularly highlighting the immune response of the host vaginal epithelium. Methods: Thirty Female Sprague-Dawley rats were divided into 5 groups; group 1: no intervention, group 2: ovariectomy group, while animals ingroups 3-5 were subjected to ovariectomy, and intravaginal inoculation of Candida albicans (C. albicans) to establish VVC. Animals in groups 4 and 5 received intravaginal lactobacilli treatment with L. acidophilus (LA-5®) and L. johnsonii (B-2178) strains, respectively for 7 days. C. albicans load was measured in the vaginal lavage 1, 3, and 7 days after stoppage of the treatment. Histological, morphometric and immunohistochemical studies of the vaginal tissues were done. IFN-γ, IL-4, and IL-17, were measured in the vaginal tissue. Results: Both L. johnsonii and L. acidophilus significantly reduced C. albicans vaginal load (250±77.46 & 133.33±40.82 CFU/mL) compared to count before treatment in both groups (4850±1419.51 & 4966.67±852.45 CFU/mL) even after 7 days of stoppage of lactobacilli treatment. A statistically significant reduction of the pro-inflammatory cytokines IL-17 and IFN- was reported in both treated groups compared to the infected untreated group. L. johnsonii has a significant effect on reduction of hyphae formation of C. albicans as well as the nuclear factor kappa B (NF-κB) immunostaining density of vaginal tissue compared to L. acidophilus. Moreover, treatment with L. johnsonii significantly minimized the epithelium damage triggered by C. albicans infection and restored normal vaginal architecture as evidenced by the histologic and morphometric studies when compared to L. acidophilus. Conclusion: Through maintaining an immune tolerant state in the vaginal epithelium and ameliorating the undesirable uncontrolled inflammatory response in the vaginal tissue, L. johnsonii (B-2178) has the potential to be utilized alone or in combination with other lactobacilli species in probiotic clinical trials to treat or prevent VVC.